Identification of Stromal Cells in Spleen Which Support Myelopoiesis - Lim, Hong Kiat; O’Neill, Helen C. (Frontiers in Cell and Developmental Biology, 2019)
Stromal cells in spleen organise tissue into red pulp, white pulp and marginal zone and also interact with hematopoietic cells to regulate immune responses. This study has used phenotypic information of a previously described spleen stromal cell line called 5G3, which supports restricted hematopoiesis in vitro, to identify an equivalent stromal cell subset in vivo and to test its capacity to support hematopoiesis. Using stromal cell fractionation, phenotypic analysis, as well as cell growth and hematopoietic support assays, the Sca-1+gp38+Thy1.2+CD29+CD51+ fraction of spleen stroma has been identified as an equivalent stromal subset resembling the 5G3 cell counterpart. While heterogeneity may still exist within that subset, it has been shown to have superior hematopoietic support capacity compared with the 5G3 cell line, and all other spleen stromal cell fractions tested.